PENGEMBANGAN MEDIA PEMBELAJARAN PUZZLE CARD BERBASIS ESD PADA MATERI BANGUN DATAR UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DI SEKOLAH DASAR - Setiawan, Bramianto; Rahman, Tita Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop an Education for Sustainable Development (ESD)-based Puzzle Card learning media to enhance elementary students’ creative thinking skills in the topic of plane figures. The research employed the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. The subjects were third-grade students at SDN Pengasinan IX, divided into experimental and control groups. Data were collected through creative thinking tests, teacher response questionnaires, and student response questionnaires. The findings indicate that the ESD-based Puzzle Card media effectively improved students’ creative thinking skills, demonstrated by the N-Gain analysis, which shows a higher increase in the experimental group compared to the control group. The implementation of this media made learning more interactive and engaging while integrating sustainability values in accordance with the Merdeka Curriculum. This study concludes that ESD-based Puzzle Cards are feasible, practical, and effective to be used as innovative learning media in mathematics, particularly in developing creative thinking skills among elementary school students.